Establishing the patient acceptable symptom state for patient-reported pain outcomes 6 months after breast cancer surgery - Matthew Kang; David Rice; Nuala Helsby; Andrew Somogyi; Michal Kluger; Daniel Chiang (PAIN Reports)
Abstract. Introduction:. The patient-acceptable symptom state (PASS) is a threshold score on patient-reported outcome measures beyond which patients consider their symptoms unacceptable (PASS negative). The PASS may guide the interpretation of outcomes associated with persistent pain after breast cancer surgery (PPBCS). Objectives:. This study aimed to identify PASS cut-off values for the numerical rating scale (NRS) on the brief pain inventory (BPI) items for pain at 6 months after breast cancer surgery and describe functional and psychological outcomes associated with an unacceptable (PASS-negative) pain state. Methods:. This prospective cohort study included patients undergoing primary breast cancer surgery. Patients were assessed preoperatively and postoperatively at 2 weeks and 6 months using validated questionnaires. Patient-acceptable symptom state was evaluated at 6 months after surgery. Patients were classified into PASS-positive (acceptable pain state) or PASS-negative groups using a pain-specific anchor question. Patient-acceptable symptom state thresholds for the BPI items were determined using the Youden index on a receiver operating characteristic curve. Results:. Of the 140 included patients, 13.6% reported a PASS-negative state at 6 months after surgery. Compared to PASS-positive patients, PASS-negative patients reported greater pain severity, pain interference, psychological distress, upper limb disability, and neuropathic pain (all P < 0.008). Numerical rating scale patient-acceptable symptom state cut-off values for the BPI items were 1.5 (worst pain), 0.5 (average pain), and 0.8 (pain interference). Conclusion:. The NRS scores for the BPI worst pain >1.5, average pain >0.5, and pain interference >0.8 delineated patients with “unacceptable” PPBCS. These values may define clinically meaningful PPBCS and offer pain cut-off values for research.